Health related quality of life over time in german sarcoma patients: an analysis of associated factors - results of the PROSa study - Eichler, Martin; Hentschel, Leopold; Singer, Susanne; Hornemann, Beate; Richter, Stephan; Hofbauer, Christine; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Jakob, Jens; Grützmann, Robert; et al. (Frontiers in endocrinology, 2023)
IntroductionSarcomas are rare cancers and very heterogeneous in their location, histological subtype, and treatment. Health-Related Quality of Life (HRQoL) of sarcoma patients has rarely been investigated in longitudinal studies.MethodsHere, we assessed adult sarcoma patients and survivors between September 2017 and February 2020, and followed-up for one year in 39 study centers in Germany. Follow-up time points were 6 (t1) and 12 months (t2) after inclusion. We used a standardized, validated questionnaire (the European Organisation for Research and Treatment of Cancer Quality of Life Core Instrument (EORTC QLQ-C30) and explored predictors of HRQoL in two populations (all patients (Analysis 1), patients in ongoing complete remission (Analysis 2)) using generalized linear mixed models.ResultsIn total we included up to 1111 patients at baseline (915 at t1, and 847 at t2), thereof 387 participants were in complete remission at baseline (334 at t1, and 200 at t2). When analyzing all patients, HRQoL differed with regard to tumor locations: patients with sarcoma in lower extremities reported lower HRQoL values than patients with sarcomas in the upper extremities. Treatment which included radiotherapy and/or systemic therapy was associated with lower HRQoL. For patients in complete remission, smoking was associated with worse HRQoL-outcomes. In both analyses, bone sarcomas were associated with the worst HRQoL values. Being female, in the age group 55-<65 years, having lower socioeconomic status, and comorbidities were all associated with a lower HRQoL, in both analyses.DiscussionHRQoL increased partially over time since treatment and with sporting activities. HRQoL improved with time since treatment, although not in all domains, and was associated with lifestyle and socioeconomic factors. Bone sarcomas were the most affected subgroup. Methods to preserve and improve HRQoL should be developed for sarcoma patients.
Veröffentlicht: 29. August 2023
Gesehen am 14.11.2023